Learning Model Problem Based Learning, Direct Learning, Thinking Styles and Their Influence on Learning Outcomes of Citizenship Education for Grade 9 Students of State Junior High School 1 Kawangkoan. - Lonto, Apeles L.; Delly, Wua Telly; Ratu, Jan A.; Rorimpandey, Widdy H. F.; Umbase, Ruth Sriana (SHS Web of Conferences, 2022)
This study aims to examine the differences in Civics learning outcomes of students who are taught by the Problem Based Learning (PBL) model and students who are taught by the Direct Learning model of grade 9 State Junior High School 1 Kawangkoan, differences in Civics learning outcomes of students who have divergent and convergent thinking styles in grade 9 State Junior High School 1 Kawangkoan, and examines the interaction between the use of learning models and thinking styles on Civics learning outcomes for grade 9 students of State Junior High School 1 Kawangkoan. This research is a quasiexperimental 2x2 factorial design. The research subjects were 9th-grade students of State Junior High School 1 Kawangkoan for the academic year 2021//2022. Collecting data using a questionnaire to distinguish students' thinking styles and learning outcomes tests conducted after learning. The data analysis technique used is a two-way 2x2 analysis of variance (ANOVA) technique with the help of the SPSS. program.